2018
DOI: 10.1161/atvbaha.118.310848
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Post-Transcriptional Regulation of Zebrafish tie1 mRNA by Long Noncoding RNA During Brain Vascular Assembly

Abstract: Objective Tyrosine kinase containing immunoglobulin and epidermal growth factor homology1 (Tie1), an endothelial and hematopoietic cell-specific receptor tyrosine kinase, is an important regulator of angiogenesis and critical for maintaining vascular integrity. The post-transcriptional regulation of tie1 mRNA expression is not understood, but it might partly explain Tie1’s differential expression pattern in endothelium. Following up on our previous work that identified natural antisense transcripts from the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
5
18
0
Order By: Relevance
“…We found that tielAS selectively binds tie1 mRNA in the cytoplasm and that overexpression of tielAS downregulates tie1 mRNA levels, causing defects in endothelial cell contacts that result in abnormal intersomitic vessel formation in the zebrafish trunk [11]. Our recent work elucidates the mechanism [23]. Using several novel technologies, which will be discussed later in this review, we demonstrated that zebrafish tielAS lncRNA forms a complex with embryonic lethal and abnormal vision Drosophila-like 1 (Elavl1, an RNA-binding protein) to regulate tie1 mRNA levels in specific tissues in the head across a small window of time [23].…”
Section: Vascular Patterning Genes (Tie1 and Dll4)mentioning
confidence: 72%
See 1 more Smart Citation
“…We found that tielAS selectively binds tie1 mRNA in the cytoplasm and that overexpression of tielAS downregulates tie1 mRNA levels, causing defects in endothelial cell contacts that result in abnormal intersomitic vessel formation in the zebrafish trunk [11]. Our recent work elucidates the mechanism [23]. Using several novel technologies, which will be discussed later in this review, we demonstrated that zebrafish tielAS lncRNA forms a complex with embryonic lethal and abnormal vision Drosophila-like 1 (Elavl1, an RNA-binding protein) to regulate tie1 mRNA levels in specific tissues in the head across a small window of time [23].…”
Section: Vascular Patterning Genes (Tie1 and Dll4)mentioning
confidence: 72%
“…Our recent work elucidates the mechanism [23]. Using several novel technologies, which will be discussed later in this review, we demonstrated that zebrafish tielAS lncRNA forms a complex with embryonic lethal and abnormal vision Drosophila-like 1 (Elavl1, an RNA-binding protein) to regulate tie1 mRNA levels in specific tissues in the head across a small window of time [23]. Thus, zebrafish tielAS post-transcriptionally regulates tie1 mRNA in a temporal and spatial manner (Figure 2).…”
Section: Vascular Patterning Genes (Tie1 and Dll4)mentioning
confidence: 88%
“…Recently, several developmentrelated lncRNAs have been identified and characterized in zebrafish and mouse (Dinger et al 2008;Pauli et al 2015;Luo et al 2016) and the results suggest that lncRNAs can substantially affect gene regulation during embryogenesis. For instance, lncRNA tie-AS was found to be involved in transcriptional regulation of vascular development (Li et al 2009;Chowdhury et al 2018). LncRNA braveheart was required for cardiovascular lineage commitment and activated the cardiac vascular gene network (Klattenhoff et al 2013;Hou et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are an important category of ncRNAs that have lengths longer than 200 nucleotides [7,8]. Recent studies have revealed that lncRNAs perform various functions in biological processes, such as cell differentiation [9], signal transduction [10] or posttranscriptional regulation [11], that are conducive to the progression of tumours and many other diseases [12]. Increasing evidence suggests that lncRNAs can work alone or in cooperation with microRNAs (miRNAs).…”
Section: Discussionmentioning
confidence: 99%